A Simple and New Method for the Synthesis of Dihydropyrimidinones by Biginelli Reaction - Jafari, H.; Gholivand, Kh.; Zare, K. (Asian Journal of Chemistry, 2011)
Borax/phosphorous oxychloride (BPO) is found to be a new efficient catalyst for three component coupling of b-dicarbonyl compounds, aldehydes and urea (or thiourea) to afford the corresponding dihydropyrimidinones or their sulfur analogues. The reaction proceeds efficiently under solventfree conditions with excellent yields.